Implikasi struktur kunci air ke atas aktiviti pelancongan dan penduduk di sekitar Sungai Chini dan Tasik Chini, Pahang - Sulong Mohamad,; Mohd Ekhwan Toriman, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2006)
Physically, water barrage structures are designed to control water level in rivers and water catchments. The construction of water barrages must take into consideration the ecosystem particularly if involves significant change of water level. Seasonal water level fluctuations at Chini Lake require the construction of water barrage at the mouth of Chini River so as to ensure optimum water level for tourist boats during dry seasons. The construction of the water barrage however affects local tourism and human activities. This article discusses the impacts of the construction of water barrage on tourism activity and local people living along the shore of Chini Lake. Based on primary and secondary data, the study finds that Chini Lake has good potential as an ecotourism destination. This article concludes that the construction of the water barrage in 1995 has resulted in negative implications to environment and the local people. These negative environmental and social impacts could have been avoided if the views of the local people are taken into account in the planning and construction of the water barrage